Zagubione dziedzictwo ideowe „Solidarności”. O ewolucji solidarnościowej myśli społeczno-politycznej w latach 1980-1989 - Krzysztof Brzechczyn, Krzysztof Brzechczyn (Człowiek i Społeczeństwo, 2016)
The paper aims to trace development of socio-political thought of “Solidarność” in years 1980-1989 in the light of a model of doctrinal evolution. In the second chapter theoretical assumptions regarding the nature of real socialism, structure of “Solidarność” movement and doctrinal development are presented. In the third chap¬ter the intellectual development of “Solidarność” thought is outline. It is supposed that in years 1980-1989 “Solidarność” was revolutionary (1980-1981) conspirational (1981-1986) and reformist social movement (1986-1989) what influenced its doctrinal development and diversification (emerging of radical and compromise wings). In the fourth chapter, the sociopolitical and socio-economic factors and conditions are identified which influenced the doctrinal development of “Solidarność” after 1989 – namely acceptance of neo-liberal model of transformation and resignation from workers’ self-governance.